1996
DOI: 10.1007/s002280050131
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin distribution in the plasma and tissues of patients infected with Onchocerca volvulus

Abstract: Infection with O. volvulus does not affect the pharmacokinetics of ivermectin, and filarial infected tissues and parasites themselves do take up the drug. There may be prolonged retention of ivermectin because of depot formation in fat tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 16 publications
9
88
1
1
Order By: Relevance
“…In such patients, plasma concentration of 52.0 ng/mL have been achieved in 5.2 hours, with an area under the curve over 48 hours of 2852 ng • h/mL. 32 Similar pharmacokinetics have been reported in healthy male volunteers receiving a 14-mg capsule of radiolabeled ivermectin. In these subjects, the mean T max was 6 hours, with a half-life of 11.8 hours.…”
supporting
confidence: 53%
“…In such patients, plasma concentration of 52.0 ng/mL have been achieved in 5.2 hours, with an area under the curve over 48 hours of 2852 ng • h/mL. 32 Similar pharmacokinetics have been reported in healthy male volunteers receiving a 14-mg capsule of radiolabeled ivermectin. In these subjects, the mean T max was 6 hours, with a half-life of 11.8 hours.…”
supporting
confidence: 53%
“…After an initial decrease, both groups showed a tendency for a second rise in plasma levels (mostly occurring between 6 and 12 h after the dose) suggesting an enterohepatic recycling of the drug (12).…”
Section: Absorptionmentioning
confidence: 94%
“…No differences in the elimination half-life were detected among healthy and onchocerciasis subjects (12). It was also suggested that the kinetics of ivermectin (its elimination halflife is around a day) were somewhat disconnected from its pharmacodynamics (antiparasitic events persisting for several months after a single dose of the drug) (11).…”
Section: Eliminationmentioning
confidence: 99%
“…Following oral administration, mean peak plasma concentration occurs approximately 4 h after dosing, a second peak at 6-12 h probably arising because of enterohepatic recycling of the drug, with the plasma half-life of ivermectin being around 12 h. [32][33][34] Dermal microfilarial loads are reduced by 78% within 2 days, and by some 98% within 2 weeks of treatment, remaining at extremely low levels for about 12 months. As lowest levels of microfilariae occur well after ivermectin administration, they are not necessarily killed when plasma drug levels are highest.…”
Section: The Present: a Puzzlementioning
confidence: 99%